2020
DOI: 10.3390/ijerph17020579
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Interpersonal Correlates of Internet Gaming Disorders among Chinese Adolescents

Abstract: This study investigated the prevalence and interpersonal correlates of Internet gaming disorders (IGD) among Chinese adolescents. A cross-sectional survey was conducted in two cities (Shanghai and Xi’an) in China. A total of 2666 (Meanage = 12.77 ± 0.75) year-one students from eight middle schools completed a self-reported questionnaire. It tested their levels of IGD, parental psychological control, negative interpersonal events (physical/verbal abuse by parents, verbal abuse by teachers, peer/online bullying)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 42 publications
9
57
0
Order By: Relevance
“…In rural Thailand, 5.4% reached the cutoff for IGD [35], and in Taiwan 3.1% met that threshold [17]. Among 2666 urban middle school children in China, prevalence of IGD was 13.0% [36]. Finally, in rural South Korea, the prevalence of PIU was 21.6% among a sample of 1168 13-to 18-year-olds [37].…”
Section: Prevalencementioning
confidence: 93%
See 1 more Smart Citation
“…In rural Thailand, 5.4% reached the cutoff for IGD [35], and in Taiwan 3.1% met that threshold [17]. Among 2666 urban middle school children in China, prevalence of IGD was 13.0% [36]. Finally, in rural South Korea, the prevalence of PIU was 21.6% among a sample of 1168 13-to 18-year-olds [37].…”
Section: Prevalencementioning
confidence: 93%
“…Throughout early adolescence PIMU increases with age, but peaks around 15-16 [39]. Indicators of lower socioeconomic status including less maternal education and a single parent household have been shown to increase the risk for PIMU [36].…”
Section: Potential Determinants Of Pimumentioning
confidence: 99%
“…24 Previous harassment, physical or verbal violence, bullied by friends, and have dissociation attitude can be the predictor factors of online gaming addiction. 17,18 Individual with previous neglect or emotional torture can lead to emotional dysregulation or inability to control emotion in daily life. 35 Predisposing factors: Biological, Psychological, and Sociocultural Sociocultural predisposing factors are individual with social problems or ability of socializing in real life.…”
Section: Discussionmentioning
confidence: 99%
“…Based on two observational studies and one case study conducted in the U.K., they developed a reference model for designing interactive online platforms to intervene DA with peer groups, as well as a process model (i.e., COPE.er) for building a customizable online environment for different disease groups. Echoed with the aforementioned findings on interpersonal risk/protective factors [17][18][19], both interventions involved interpersonal elements.…”
mentioning
confidence: 86%
“…As aforementioned, need dissatisfaction for relatedness was identified as a risk factor of IGD for Chinese young adults by Hui et al [17]. Yang et al [18] found four types of interpersonal stressors that may exacerbate adolescent IGD, which include parental psychological control, physical/verbal abuse by parents, verbal abuse by teachers, and peer/online bullying (N = 2666). In addition to the neurotic personality trait, Chang et al [19] also revealed that the wish to develop new interpersonal relationships online was a potential antecedent of IA among young adults in Taiwan (N = 223), via the mediating effect of anxiety during online interpersonal interactions.…”
mentioning
confidence: 98%